AB0962 UPDATE FOR THE CLINICAL PRACTICE: INTEGRATED, EVIDENCE-BASED APPROACH FOR THE MANAGEMENT OF JUVENILE SPONDYLOARTHRITIS. (June 2019) - Eissa, Mervat; Miedany, Yasser El; Hassan, Waleed; Mekkawy, Dalia; Mortada, Mohammed A.; Nasef, Samah Ismail; Gaafary, Maha El; Lotfy, Hala; Farag, Yomna; Deriny, Ghada El; Abu-Zaid, Mohammed Hassan; Atef, Yossra; et al.
Abstract : Background: Juvenile onset spondyloarthritis (SpA) is a heterogeneous group of human leukocyte antigen (HLA) -B27 associated inflammatory syndromes that affect children and adolescents under the age of 16 years No specific recommendations for the treatment of juvenile spondyloarthritis have been established. Important differences exist between spondyloarthritis in children and adults, supporting the need for pediatric-specific recommendations. Objectives: To set recommendations for the management of children and adolescents with spondyloarthritis. Methods: Searching Medline for Juvenile spondyloarthritis management was done. A systematic literature search was conducted to collect the existing recommendations, guidelines involved line of treatment for Juvenile SpA & adult SpA. These included 2011 ACR recommendations for the treatment of JIA and the 2016 update of the ASAS-EULAR management recommendations for axial spondyloarthritis. Results: NSAIDs have been shown to improve symptoms, reduce inflammatory lesions and may slow spinal radiographs progression with continuous use. Glucocorticoid injections directed to the local site of musculoskeletal inflammation may be considered. Sulfasalazine may be considered in patients with peripheral arthritis. Initiation of a (tumor necrosis factor inhibitor (TNFi) was recommended for patients with active sacroiliac arthritis who have received an adequate trial of NSAIDs. Also, it should be initiated to those who fail to respond to synthetic disease modifying anti-rheumatic drugs (sDMARD). If TNFi therapy fails, switching to another TNFi should be done. If a patient is in sustained remission, tapering of a biological DMARD can be considered. Conclusion: These guidelines provide up-to-date guidance on the management of patients with juvenile SpA, based on combining evidence and expert opinion. Disclosure of Interests: None declared